Unity in power, power in unity: Why the EU needs more integrated electricity markets - Georg Zachmann; Carlos Batlle; Francois Beaude; Christoph Maurer; Monika Morawiecka; Fabien Roques (Bruegel, 2024)
The energy crisis that started in 2022 reminded European governments of the resilience provided by relatively well-integrated European electricity markets. European Union leaders thus decided to reverse a creeping energy renationalisation and to invest in completing the internal market. However, there are indications this momentum is being lost, with different EU capitals taking different lessons from the energy crisis, at a time of unprecedented investment needs in generation and grids. The multiple benefits of enhanced EU energy-market integration should be emphasised. 'Techno-economic' benefits can be secured from optimising the design and operation of several national electricity systems jointly, rather than individually. These benefits will increase massively with higher shares of renewables and include less fossil-fuel burn and less volatile short-term prices, cost savings through harnessing regional renewables advantages, reduced need for expensive back-up capacity and flexibility, and enhanced resilience to shocks. In addition, greater energy-market integration will trigger benefits of a more managerial-governance related nature. These include benefits in terms of competition, innovation and credibility, which are particularly useful in the electricity sector, which typically faces long investment times and high degrees of concentration in purely national markets. Further market integration requires substantial political investment. Governments will need to deal with significant distributional effects within and between countries. Domestic political constraints in this respect are often numerous and difficult to overcome. Therefore, achieving the benefits of integration will require a vision on what degree of integration is feasible and desirable, and how to properly implement and govern it. It will also require an honest acknowledgement of the implications and costs of not pursuing greater integration.
Keywords: 330